Quality of Work Life And Medical Teachers' Commitment: A moderated mediation analysis of fear of COVID-19 and job satisfaction - Gaurav Deep Rai; Saurabh Verma (ACHSM, 2023)
This study is principally the first to test a moderated mediation model of COVID-19 fear and job satisfaction in the Quality of Work Life (QWL)-commitment relationship of medical teachers during the pandemic. The conceptual model draws its theoretical tenet from spillover and conservation of resources theories. Cluster sampling was incorporated from four metropolitan cities in India. A mixed-method research design was administered to 378 medical teachers amidst the pandemic. The partial least squares structural equation modeling (PLS-SEM) results indicate a significant positive association between the constructs. Path analyses have highlighted positive associations between QWL, job satisfaction, and affective commitment to medical institutions. Further, a partial mediation effect of job satisfaction in the QWL-commitment relationship is highlighted, adding a new dimension to past studies. Intriguingly, each of the positive associations between QWL, job satisfaction, and commitment was negated and significantly moderated by the fear of COVID-19 experienced by the medical teaching fraternity. The findings offer practical implications to the stakeholders (Ministry of Health and Family Welfare, Department of Higher Education, Government of India, and State Governments) in enriching the QWL, job satisfaction, and medical teachers' commitment induced by psychological stress, anxiety, role conflict, post-traumatic stress disorder, and fear of COVID-19 in the global pandemic.